Exponential Functions Permit Estimation of Anaerobic Work Capacity and Critical Power from Less than 2 Min All-Out Test - Ming-Chang Tsai; Scott Thomas; Marc Klimstra (Algorithms)
The Critical Power Model (CPM) is key for assessing athletes’ aerobic and anaerobic energy systems but typically involves lengthy, exhausting protocols. The 3 min all-out test (3MT) simplifies CPM assessment, yet its duration remains demanding. Exponential decay models, specifically mono- and bi-exponential functions, offer a more efficient alternative by accurately capturing the nonlinear energy dynamics in high-intensity efforts. This study explores shortening the 3MT using these functions to reduce athlete strain while preserving the accuracy of critical power (CP) and work capacity (<semantics>W′</semantics>) estimates. Seventy-six competitive cyclists and triathletes completed a 3MT on a cycle ergometer, with CP and <semantics>W′</semantics> calculated at shorter intervals. Results showed that a 90 s test using the bi-exponential model yielded CP and <semantics>W′</semantics> values similar to those of the full 3MT. Meanwhile, the mono-exponential model required at least 135 s. Bland–Altman and linear regression analyses confirmed that a 120 s test with the mono-exponential model reliably estimated CP and <semantics>W′</semantics> with minimal physical strain. These findings support a shortened, less-demanding 3MT as a valid alternative for CPM assessment.